Pengaruh Digital Marketing terhadap Keputusan Pembeli Online - Qibtiyana, Mariyatul; Ali, Hapzi (Jurnal Humaniora, Ekonomi Syariah dan Muamalah, 2023)
Changes in information technology on consumer behavior, especially from offline to online shopping. This digital marketing, including digital marketing and influencer marketing, is a key strategy for reaching consumers. Purchasing decisions are influenced by price, service quality and influencer influence, which require encouragement and consumer trust. Digital marketing, influencer marketing, and service quality are key elements in an effective business strategy in the digital era. Companies that are able to adapt and take advantage of these developments will be more competitive and able to face market changes. Therefore, understanding digital market dynamics and implementing the right strategy is crucial to meeting consumer needs and achieving optimal growth. The influence of digital marketing on online buyers' decisions aims to determine the influence of potential buyers' decisions. This article uses data collection and analysis methods which are carried out by searching for literature studies and observations with previous sources saying the results of this article are that Digital Marketing, Influencer Marketing, Service Quality influence online buyer decisions